The wade test: Generative AI and a CEO bot - Prithwiraj Choudhury; Bart S. Vanneste; Amirhossein Zohrehvand (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Generative AI (Gen-AI) is increasingly used to communicate on behalf of organizational leaders. We investigate whether Gen-AI can mimic a CEO and whether employees display aversion to its communication. We present a framework distinguishing between a strong or weak form of Gen-AI aversion. In a field experiment, employees evaluated responses from their CEO ("Wade") and an AI bot trained on the CEO's communication. Employees correctly identified the source 59% of the time, yet rated responses believed were AI-generated as less helpful, regardless of actual source. A second study with a general audience directly manipulates AI labels and likewise finds AI-labeled responses are rated as less helpful. Together, the findings provide evidence of strong algorithm aversion to Gen-AI used as a CEO bot.
Keywords: O15; M54; 330; Generative AI; algorithm aversion; CEO communication